2022
DOI: 10.3390/jcm11206057
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition, Fasting Blood Glucose and Lipidemic Indices Are Not Primarily Determined by the Nutritional Intake of Middle-Aged Endurance Trained Men—Another “Athletes’ Paradox”?

Abstract: Systematic, regular high-volume endurance training induces significant metabolic adaptations in glucose and lipids metabolism, which seems to affect the negative impact of unhealthy nutrition, at least in animal models. The present study aimed to investigate the main determinants of body composition, blood glucose and lipids concentrations between middle-aged sedentary individuals (Sed) and well-trained endurance athletes (Run), both following an unhealthy high-fat diet. In thirty-five Sed (Age: 54.0 ± 6.6 yrs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Both of these studies emphasize the importance of exercise for metabolic health across the lifespan, which is echoed in recent studies examining the role exercise has in metabolic-related chronic diseases [ 12 , 13 , 14 , 15 ]. A recent review highlighted the importance of resistance training for improving outcomes in the early and late stages of frailty and sarcopenia [ 15 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Both of these studies emphasize the importance of exercise for metabolic health across the lifespan, which is echoed in recent studies examining the role exercise has in metabolic-related chronic diseases [ 12 , 13 , 14 , 15 ]. A recent review highlighted the importance of resistance training for improving outcomes in the early and late stages of frailty and sarcopenia [ 15 ].…”
mentioning
confidence: 99%
“…For example, in females across the lifespan (ages 20–60 years), a combination of aerobic and resistance training improved risk factors of metabolic syndrome, including waist circumference, fasting blood glucose, blood pressure, and blood lipid parameters [ 12 ]. Additionally, Methenitis et al examined differences in body composition, blood glucose, and lipid concentrations in sedentary compared to endurance-trained middle-aged adults consuming a high-fat diet [ 14 ]. This study found that training-induced energy expenditure is the main determinant of these metabolic parameters, as well as positive metabolic adaptations that were more influenced by exercise training rather than nutritional intake.…”
mentioning
confidence: 99%
See 1 more Smart Citation